2021
DOI: 10.1002/smi.3045
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and changes in depressive symptoms among postgraduate students: A systematic review and meta‐analysis from 1980 to 2020

Abstract: Education actively helps us develop our well-being and health, but postgraduate students are at high risk of depression. The prevalence of depression symptoms varies from 6.2% to 84.7% among them, and its changes throughout the years remains unclear. The present study aimed to estimate the real prevalence of depression symptoms among postgraduate students and the changes from 1980 to 2020. Thirty-seven primary studies with 41 independent reports were included in the meta-analysis (none reports were in high-qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 101 publications
1
5
0
Order By: Relevance
“…In contrast to the present study, Nikčević’s findings suggest that openness to personality may hinder depression ( Nikcevic et al, 2021 ). The results of previous studies were also consistent with the findings of these factors ( Bum and Jeon, 2016 ; Watson et al, 2019 ; Guo et al, 2021 ). Age and monthly income per capita influence depression in the media use low-frequency group.…”
Section: Discussionsupporting
confidence: 90%
“…In contrast to the present study, Nikčević’s findings suggest that openness to personality may hinder depression ( Nikcevic et al, 2021 ). The results of previous studies were also consistent with the findings of these factors ( Bum and Jeon, 2016 ; Watson et al, 2019 ; Guo et al, 2021 ). Age and monthly income per capita influence depression in the media use low-frequency group.…”
Section: Discussionsupporting
confidence: 90%
“…Our survey demonstrated that mental health distress remained common among medical and non-medical postgraduates, even when the COVID-19 situation was improving. In this study, 36.2% of postgraduates reported moderate or higher levels of depression symptoms, which was more severe than before the COVID-19 outbreak (27%) [ 46 ] and during the pandemic (34%) in China [ 47 ]. Our results were similar to those of surveys carried out among the general population during periods without lockdowns in China [ 48–53 ], while higher than the results obtained from healthcare workers in Singapore one year after the outbreak [ 54 ].…”
Section: Discussionmentioning
confidence: 93%
“…Due to the influence of multiple factors, such as individual, family and school, the psychological pressure of graduate students in colleges and universities is higher than that of the general population on the whole, and their mental health status is also worse ( Guo et al., 2021 ). For students, experience of high academic stress was associated with low life satisfaction ( Moksnes et al., 2019 )coupled with the fact that medical education itself is a highly stressful process ( Iftikhar et al., 2019 ), which can reduce medical students’ life satisfaction ( Wang et al., 2019 ).…”
Section: Introductionmentioning
confidence: 99%